2002
DOI: 10.1037/0022-0167.49.3.376
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of client emotion in helpful sessions of cognitive-behavioral and psychodynamic-interpersonal therapy.

Abstract: Whereas cognitive-behavioral (CB) therapy sessions aim to be instructive and encouraging, psychodynamic-interpersonal (PI) sessions aim to be exploratory and may be emotionally painful. Raters rated degree of pleasure and arousal in each sentence of client speech in CB and PI sessions (N ϭ 18) that therapists had identified as particularly helpful. Client emotion in PI sessions was less pleasant, on average, than client emotion in CB sessions; emotion was most negative in the middle of the PI sessions. Within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Although the client still misses his loved one, feelings tend to become more neutral, since this experience progressively has less impact in the client's life. Early work comparing APES ratings with sentence-by-sentence coding of affect was consistent with this account (Mackay et al, 2002).…”
Section: (Figure 1)mentioning
confidence: 74%
“…Although the client still misses his loved one, feelings tend to become more neutral, since this experience progressively has less impact in the client's life. Early work comparing APES ratings with sentence-by-sentence coding of affect was consistent with this account (Mackay et al, 2002).…”
Section: (Figure 1)mentioning
confidence: 74%
“…Goldfried, Castonguay, Hayes, Drozd and Shapiro (1997) also compared sessions from CBT and PI therapies and, although they used a different methodology, they concluded with virtually identical results in relation to emotion: it was a prominent component of therapy in PI therapy but not in CBT therapy. In another study comparing helpful sessions of CBT and PI therapy, Mackay, Barkham, Stiles and Goldfried (2002) found that CBT therapy tended to be more instructional and less exploratory than PI therapy, that emotion in PI therapy was, on average, less pleasant and more painful than in CBT therapy, and that whereas emotional arousal followed a U pattern in CBT therapy with the middle of the session being calmest, in PI therapy it involved an inverted U, with arousal of painful affect being highest in the middle of the session and then dropping off. Coombs, Coleman and Jones (2002) studied the therapists' stance toward client emotion in 128 sessions of CBT and IPT for depression.…”
Section: Emotional Processing and Exposure Therapymentioning
confidence: 98%
“…Her level of expressed emotional arousal, however, was judged to be very low on the basis of observer ratings of emotional arousal from videotaped therapy segments. In a study on helpful sessions (Mackay, Barkham, Stiles, & Goldfried, 2002), in productive sessions of psychodymanicinterpersonal therapy the arousal of unpleasant emotion followed an inverted-U pattern against time, as the highest arousal of painful feelings took place in the middle of the session and had attenuated by the end of the session. The practice implication, then, is that emotional processing is best facilitated by the progressive increase and then attenuation of expressed emotional arousal over the course of a session.…”
Section: Emotion Awareness and Arousalmentioning
confidence: 99%